2010
DOI: 10.1590/s0103-64402010000300003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atorvastatin in radiographic density on alveolar bone loss in wistar rats

Abstract: The purpose of this study was to evaluate the effect of Atorvastatin (ATV) on alveolar bone loss induced in rats. Periodontitis was induced by ligature placement around the upper second left molar in a total of 24 male Wistar rats (± 200 g). Groups of 6 animals received via oral gavage either saline or ATV (1, 3 and 9 mg/kg) during 11 days. After this time, the animals were sacrificed and their maxillae were removed, defleshed, radiographed by Digora System®, and latter stained to be photographed using a digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 20 publications
6
54
0
2
Order By: Relevance
“…Moreover, a decrease in gingival bleeding was also greater in ATV as compared to SMV group, thus suggesting a potent anti-inflammatory action of ATV. A similar anti-inflammatory effect of statins was observed by Lindy et al 11 in patients with CP, who were on systemic statin therapy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, a decrease in gingival bleeding was also greater in ATV as compared to SMV group, thus suggesting a potent anti-inflammatory action of ATV. A similar anti-inflammatory effect of statins was observed by Lindy et al 11 in patients with CP, who were on systemic statin therapy.…”
Section: Discussionsupporting
confidence: 80%
“…9,10 Statin users have been found to have improved periodontal condition as compared to non-statin users. 11,12 Recently, our studies showed that local delivery of statins, 1.2% SMV and 1.2% ATV, into periodontal pocket stimulates a significant increase in the PD reduction, relative attachment (RAL) gain, and improved radiographic defect depth reduction as compared to placebo gel as an adjunct to scaling and root planing (SRP) in the treatment of CP and individuals with type II diabetes and CP. 13-16 …”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that this method may result in the exclusion of some trabecular bone from the analysis. While this represents a limitation of our research, it is positively comparable with limitations faced by other researchers who have previously attempted to identify the changes of mandibular bone as a result of osteoporosis, whether it was based on 2D X-ray [41][42][43] or 3D CT. 33,44,45 All of these studies were challenged by the difficulty of acquiring a standard VOI for comparison between animals and between experimental groups. We believe that the creative method developed in this study for defining the VOI in the maxilla may also be used for other applications in bones of irregular shape.…”
Section: Discussionsupporting
confidence: 56%
“…Some in vivo studies have suggested that statins are beneficial for treatment of bone fractures and osteoporosis [13,20,[28][29][30][31][32][33][34][35][36]38,39,[99][100][101][102]. However, other in vivo investigations have stated that statins may have no benefit in such cases [15,34,35,[40][41][42][43].…”
Section: Discussion and Future Prospectivementioning
confidence: 99%
“…In both the animal and clinical studies, simvastatin and atorvastatin are the most investigated statin types so that the majority of the studies suggest their beneficial metabolic effects on bone [20,22,27,[28][29][30][31][32][33][34][35][36]38,39,[99][100][101][102][103][104][105][106][108][109][110][111][112][113][114]. However, very few studies evaluated the role of other family members including rosuvastatin [99,105], lovastatin [37,109], fluvastatin [33,39], cerivastatin [40] and pravastatin [26,101].…”
Section: Discussion and Future Prospectivementioning
confidence: 99%